Recovery and Biodistribution of Ex Vivo Expanded Human Erythroblasts Injected into NOD/SCID/IL2Rγ(null) mice - Ghinassi, Barbara (SAGE-Hindawi Access to Research, 2011)
Ex vivo expanded erythroblasts (EBs) may serve as advanced transfusion products provided that lodgment occurs in the macrophage-niche of the marrow permitting maturation. EBs expanded from adult and cord blood expressed the receptors (CXCR4, VLA-4, and P-selectin ligand 1) necessary for interaction with macrophages. However, 4-days following transfusion to intact NOD/SCID/IL2Rγ(null) mice, CD235a(pos) EBs were observed inside CD235a(neg) splenic cells suggesting that they underwent phagocytosis. When splenectomized and intact NOD/SCID/IL2Rγ(null) mice were transfused using retrovirally labeled human EBs, human cells were visualized by bioluminescence imaging only in splenectomized animals. Four days after injection, human CD235a(pos) cells were detected in marrow and liver of splenectomized mice but only in spleen of controls. Human CD235a(pos) erythrocytes in blood remained low in all cases. These studies establish splenectomized NOD/SCID/IL2Rγ(null) mice as a suitable model for tracking and quantification of human EBs in vivo.